Transmission of viral RNA and DNA to maize kernels by vascular puncture inoculation - Redinbaugh, Margaret G.; Louie, Raymond; Ngwira, Patricia; Edema, Richard; Gordon, Donald T.; Bisaro, David M. (Journal of virological methods, 2001)
Vascular puncture inoculation (VPI) is an effective technique for transmission of maize viruses without using arthropods or other biological vectors. It involves using a jeweler’s engraving tool to push minuten pins through a droplet of virus inoculum toward the major vascular bundle in the scutellum of germinating kernels. Here, VPI is shown to be useful for introducing RNA and DNA viral genomes into maize. Maize dwarf mosaic potyvirus (MDMV) virions, MDMV genomic RNA, foxtail mosaic potexvirus (FoMV) genomic RNA and maize streak geminivirus (MSV) DNA were introduced into kernels by VPI, and infection rates determined. At high concentrations, both MDMV virion and genomic RNA preparations produced 100% infection of susceptible maize. However, MDMV genomic RNA was transmitted with about 100-fold lower efficiency than virions. FoMV genomic RNA and MSV DNA were transmitted at lower efficiency than the MDMV RNA, and the highest transmission rates were about 50%. Ribonuclease A pretreatment prevented genomic MDMV and FoMV RNA transmission, but not MDMV virion transmission indicating the viral RNA was the infectious entity. Proteinase K (ProK) pretreatment reduced transmission of MDMV RNA suggesting that integrity of the viral genomic protein bound covalently to the viral RNA may be important for efficient transmission
Keywords: Maize dwarf mosaic virus; Foxtail mosaic virus; Maize streak virus; Vascular puncture inoculation